Perfil dos empreendedores e caracterização dos empreendimentos do centro comercial de Portalegre - RN - Morais Filho, Jady Clésio José de (Universidade Federal Rural do Semi-Árido, 2018)
Work on the characterization of entrepreneurs and entrepreneurs from the municipality of Portalegre/RN commerce, having as guiding principles the theoretical conceptions about entrepreneurship adopted by SEBRAE (Brazilian Service of Support for Micro and Small Enterprises), in its orientations to small and medium-sized enterprises in Brazil, Dornelas (2001; 2012) and on theoretical constructions from the following research project, Mapping of the Enterprises and its Entrepreneurs Profile from the Municipalities of the State of Rio Grande do Norte. (Code: PIF00040-2017). Prorectory of Research and Post-Graduation - PROPPG/UFERSA–Angicos/RN, 2017, that explores commercial and entrepreneurship activities in all potiguar regions. Entrepreneurs are accomplishers who develops new ideas and consequently has a huge impact in a nation economy, they are in charge of employ and contribute to the development in general, a concept that really applies in the entrepreneurial context of our region. To its development a documentary, bibliographic and field research was made at 25 enterprises, from Portalegre city’s commercial center, municipality situated in Polo Serrano of the West potiguar, in the State of Rio Grande do Norte, having as instrument a questionnaire composed of twenty-two questions, all being related to the characterization of entrepreneurs and local entrepreneurs, investigating the participants' gender, age group, type of enterprise, level of education, types of financing and technologies used by entrepreneurs to assist them in company services. For this purpose, it was essential to make a data collection the number of enterprises and then visit each one of them in order, to identify a current situation of the enterprises and familiarize with the informants. From the data obtained, it was possible to diagnose the developments and outline the profile of the city's entrepreneurs and to make a quantitative analysis of the data collected. With this, it is possible to compare data, in the future, with other cities in the region in the economic scenario and, consequently, to propose changes, aiming a better perspective of development for the population of the region.
Monografia
Keywords: Economia; Empreendedorismo; Desenvolvimento; Tecnologia; Economy; Entrepreneurship; Development; Technology; CIENCIAS EXATAS E DA TERRA::CIENCIA E TECNOLOGIA